Clinical and molecular characterization of Iranian patients with congenital fibrinogen disorders. (December 2021) - Mohsenian, Samin; Seidizadeh, Omid; Mirakhorli, Mojgan; Jazebi, Mohammad; Azarkeivan, Azita
Highlights: In patients with dysfibrinogenemia, Arg35 and Arg301 are the most common residues which affected by mutations. The p.Val145Asp and two hotspot mutations, p.Arg35His, p.Arg35Cys, were identified for the first time in Iran. There is a weak phenotype-genotype correlation in patients with congenital fibrinogen disorders. Abstract: Introduction: Congenital fibrinogen disorders (CFDs) are caused by mutations in the FGA, FGB and FGG genes and are classified as quantitative and qualitative fibrinogen defects. This study sought to determine the genetic background of CFDs in Iran and to examine the genotype-phenotype correlation. Methods: Fourteen patients with a CFD diagnosis were included. Fibrinogen antigen and activity were measured by the immunoturbidimetric and Clauss methods respectively. Gene sequencing was performed following a polymerase chain reaction amplification of fibrinogen's genes. The ISTH Bleeding Assessment Tool was also evaluated for all cases. Results: Patients were diagnosed with dysfibrinogenemia (n = 10), hypodysfibrinogenemia (n = 2) and afibrinogenemia (n = 2). Seven different mutations located on FGA exon 2 (57 %), exon 4 (7%), exon 5 (7%) and FGG exon 8 (29 %) were identified. In patients with qualitative deficiencies, mutations were including p.Arg38Thr, p.Arg35His, p.Arg35Cys, p.Val145Asp, and p.Arg301Cys and were including p.Gly316GlufsX105 and p.Trp52stop in afibrinogenemic patients. In dysfibrinogenemia, two hotspot mutations, FGA Arg35 and FGG Arg301 were identified in 60 % of patients and the remaining (40 %) had p.Arg38Thr mutation. The p.Val145Asp and two hotspot mutations, p.Arg35His, p.Arg35Cys, were identified for the first time in Iran. The overall median (range) bleeding score (BS) was 4 (0-6) in all patients and it was 3.5 (0–5) in dysfibrinogenemia. Cutaneous bleeding and menorrhagia were the most common bleeding manifestations. Conclusion: There was a weak genotype-phenotype correlation in CFDs and patients with dysfibrinogenemia were more symptomatic than in previous studies. Despite ethnic's differences, the prevalence of hotspot mutations in dysfibrinogenemia was similar to the other studies.